#### Answer

$y' = x^{2} + x - e^{-x}$
$y'' = 2x +1 +e^{-x}$

#### Work Step by Step

$y = \frac{x^{3}}{3} + \frac{x^{2}}{2}+ e^{-x}$
$y' = \frac{3x^{3-1}}{3} + \frac{2x^{2-1}}{2} - e^{-x}$
$y' = x^{2} + x - e^{-x}$
$y'' = 2x +1 +e^{-x}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = x^{2} + x - e^{-x}$
$y'' = 2x +1 +e^{-x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.